2011
DOI: 10.1136/annrheumdis-2011-200478
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis patients with nail disease have a greater magnitude of underlying systemic subclinical enthesopathy than those with normal nails

Abstract: The link between nail disease and contemporaneous subclinical enthesopathy offers a novel anatomical basis for the predictive value of nail psoriasis for PsA evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
85
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 18 publications
13
85
0
11
Order By: Relevance
“…In this study, we found a significant correlation between the disease duration and US enthesitis, which is consistent with that reported by Ozcakar et al (8) in their study on US of the Achilles tendon in patients with psoriasis and Ash et al (23) who examined the association between nail changes and subclinical enthesitis. This was contrary to that reported by Naredo et al (19) and Gutierrez et al (21).…”
Section: Achilles Enthesitis Was the Most Common Us Sign In This Studsupporting
confidence: 82%
“…In this study, we found a significant correlation between the disease duration and US enthesitis, which is consistent with that reported by Ozcakar et al (8) in their study on US of the Achilles tendon in patients with psoriasis and Ash et al (23) who examined the association between nail changes and subclinical enthesitis. This was contrary to that reported by Naredo et al (19) and Gutierrez et al (21).…”
Section: Achilles Enthesitis Was the Most Common Us Sign In This Studsupporting
confidence: 82%
“…Specifically, enthesitis is associated with adjacent osteitis or bone and synovial inflammation. Moreover, Ash ZR et al [35] demonstrated that enthesopathy scores were higher in patients with psoriatic nail disease than in patients without nail disease and healthy controls. In contrast to our results, Ash ZR et al [35] showed that no link between the psoriasis area and severity index and enthesitis was evident.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ash ZR et al [35] demonstrated that enthesopathy scores were higher in patients with psoriatic nail disease than in patients without nail disease and healthy controls. In contrast to our results, Ash ZR et al [35] showed that no link between the psoriasis area and severity index and enthesitis was evident. A possible Explanation of differences of correlation between enthesitis scores and severity of psoriasis from other authors may be due different methods of assessment of enthesopathy and severity of psoriasis as well as our patients had moderate-to-severe PsA.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the close anatomic connection between the nails and extensor digitorum tendon attachment to the bone and the periosteum, the higher prevalence of nail involvement in patients with psoriatic arthritis could be explained [42]. Recent studies underlined the existence of a link between nail psoriasis and synovio-entheseal complex in psoriatic arthritis [43][44][45].…”
Section: Psoriatic Arthropathymentioning
confidence: 99%